Placement criteria of oil and gas deposits in Dnepr-Donetsk cavity taking into account hydrochloric tectonics - Загороднов, А. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
There is a question at the search of hydrocarbon deposits: why in one regions does mainly find oil, and in other gas deposits? This article has an object on the basis of present actual material and analysis of different hypotheses and looks to ground the vision and solution of this question in the conditions of the Dniper-Donetsk depression (DDD).Hydrocarbons migrate to the places of the accumulation through the layers of sedimentary rocks. The ways of migration of hydrocarbons, changing of their phase state, speeds of passing through the layers of sedimentary rocks, are considered in the article, the question about age of hydrocarbons that are presently in traps was highlighted.As a result of the conducted researches and analysis of existent presentations the criteria of location of oil and gas deposits are identified in the conditions of the Dniper-Donetsk depression and temporal interval of hydrocarbons formation.The developed deposits of hydrocarbons are formed in recent (less than 87 thousand of years), in a geological calculation, time.A size and safety of deposits depend on a difference between speed of passing of barrier and speed of receipt of fluid in a trap, and also by a time interval, past from the moment of formation of barrier-trap.In DDD the presence of hydrocarbons deposits is determined the presence of salt tectonics which provides:- it is impulse-permanent supply of mantle fluid through the weakened zones of salt stocks.- a salt tectogenesis is one of gel-forming factors at forming of anticlinal traps for the accumulation of hydrocarbons.- intensive growth of salt stocks in Permian time provided forming of reliable salt overlay on greater part of central part of DDD.Location of oil and gas deposits is determined:- in areas with a newtectonic activity by the amount of tectonic movement, intensity of salt tectogenesis and in less degree quality of collectors in the moment of fluid filling.- in districts with low tectonic activity mainly by quality of collectors.Location of oil and gas deposits on a lateral depend on:- the presence of reliable overlay (in DDD – development of early Permian salt. If it is absent, large gas depositi are not saved).- the presence of newtectonic activity and salt tectogenesis, which are instrumental in entering hydrocarbon fluid in sedimentary cover.- long way and the speed of passage of aggressive originally methane fluid in main oil formation stage`s zone for the generation, dissolution and removal (emigration) from the rocks of heavy hydrocarbons (by passing aggressive fluid through the rocks, which are already converted to the stage of deep katagenesis and higher generation of heavy hydrocarbons not happening)